Mitos Bukit Buung Batu Majalan di Desa Adat Pengosekan: Analisis Ekologi Sastra - Dewi, Ni Putu Novsa; Suardiana, I Wayan; Duana Sutika, I Nyoman (Humanis; Vol 27 No 1 (2023)DO - 10.24843/JH.2023.v27.i01.p06, 2023)
This study is entitled "The Myth of Bukit Buung Batu Majalan in Pengosekan Traditional Village: Literary Ecological Analysis". This study aims to describe the literary ecology contained in it. This study uses the theory of literary eco-criticism. The listening method and the speaking method with recording techniques and note-taking techniques as well as using literal and idiomatic translation techniques are used in the data collection stage. The analytical descriptive method is used in the data analysis stage. Informal and formal methods are used in presenting the results of data analysis with deductive and inductive techniques. The results of this study are that this myth contains literary ecology which consists of 1) Pastoral narrative includes bucolic elements, arcadia construction elements, and elements of retreat and return discourse. 2) The apocalyptic narrative includes elements of the hero character, apocalyptic environmental elements, and elements of visions or predictions, and 3) Environmental wisdom values ??consisting of respect for nature, moral responsibility towards nature, solidarity towards nature, compassion and concern for nature, as well as the attitude of not disturbing natural life